2009
DOI: 10.1002/jcb.22319
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐2 modulates β‐catenin signaling through stimulation of Lrp5 expression and inhibition of β‐TrCP expression in osteoblasts

Abstract: Canonical BMP and Wnt signaling pathways play critical roles in regulation of osteoblast function and bone formation. Recent studies demonstrate that BMP-2 acts synergistically with β-catenin to promote osteoblast differentiation. To determine the molecular mechanisms of the signaling cross-talk between canonical BMP and Wnt signaling pathways, we have used primary osteoblasts and osteoblast precursor cell lines 2T3 and MC3T3-E1 cells to investigate the effect of BMP-2 on β-catenin signaling. We found that BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 38 publications
3
64
0
1
Order By: Relevance
“…The absence of Lrp5 specifically depletes adult regenerative stem cell activity to less than 1% [48]. It has been shown that an increased expression of Lrp5 is sufficient for activation of the canonical Wnt signaling pathway [49]. In light of our data showing that low oxygen increased Lrp5 mRNA transcript levels (Fig.…”
Section: Low Oxygen Stimulates the Canonical Wnt Pathwaymentioning
confidence: 54%
“…The absence of Lrp5 specifically depletes adult regenerative stem cell activity to less than 1% [48]. It has been shown that an increased expression of Lrp5 is sufficient for activation of the canonical Wnt signaling pathway [49]. In light of our data showing that low oxygen increased Lrp5 mRNA transcript levels (Fig.…”
Section: Low Oxygen Stimulates the Canonical Wnt Pathwaymentioning
confidence: 54%
“…Bmp2 also regulates -catenin signaling pathway during bone formation (Chen et al, 2007;Zhang et al, 2009). Regulation of the canonical WNT/-catenin pathway by TGF-/BMP signaling is an important regulatory mechanism for a number of biological processes.…”
Section: Relationships Between the Amh And Wnt/-catenin Signaling Pamentioning
confidence: 99%
“…They also suggested that the contributory effect of this up-regulation of LRP5 by 1,25(OH) 2 D 3 to the overall actions of 1,25(OH) 2 D 3 on bone remained to be determined. 35 Actually, if there is such an interaction between vitamin D and LRP5 gene expression, this might have at least partially played some part in the variation of our patients' LRP5 expression patterns.…”
Section: Discussionmentioning
confidence: 90%
“…It has been demonstrated that the expression of LRP5 in osteoblast was increased by bone morphogenetic protein 2. 35 Fretz et al 36 discovered that 1,25(OH) 2 D 3 may induce binding of the vitamin D receptor to sites within the LRP5 gene locus. This interaction is thought to cause a modification in chromatin structure within the LRP5 locus and induce LRP5 messenger ribonucleic acid transcription in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%